2014
DOI: 10.1007/s00018-014-1657-5
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecular complexes at active zones: integrated nano-machineries for neurotransmitter release

Abstract: The release of neurotransmitters from synaptic vesicles exocytosing at presynaptic nerve terminals is a critical event in the initiation of synaptic transmission. This event occurs at specialized sites known as active zones. The task of faithfully executing various steps in the process is undertaken by careful orchestration of overlapping sets of molecular nano-machineries upon a core macromolecular scaffold situated at active zones. However, their composition remains incompletely elucidated. This review provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 159 publications
1
6
0
Order By: Relevance
“…Since even poly-D-lysine-coated beads are able to induce presynaptic differentiation and local assembly of F-actin in vitro , it is suggested that cell adhesion by itself may be sufficient to induce F-actin assembly (Lucido et al, 2009 ), indicating the importance of cell-adhesion molecules in specifying the subcellular location of F-actin rearrangements. This is consistent with the emerging idea that various cell adhesion molecules often converge on a similar pathway that induces F-actin rearrangements (Nelson et al, 2013 ; Chua, 2014 ), which could ultimately lead to the capturing of SV proteins (Bury and Sabo, 2014 ) and thereby presynaptic assembly.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…Since even poly-D-lysine-coated beads are able to induce presynaptic differentiation and local assembly of F-actin in vitro , it is suggested that cell adhesion by itself may be sufficient to induce F-actin assembly (Lucido et al, 2009 ), indicating the importance of cell-adhesion molecules in specifying the subcellular location of F-actin rearrangements. This is consistent with the emerging idea that various cell adhesion molecules often converge on a similar pathway that induces F-actin rearrangements (Nelson et al, 2013 ; Chua, 2014 ), which could ultimately lead to the capturing of SV proteins (Bury and Sabo, 2014 ) and thereby presynaptic assembly.…”
Section: Introductionsupporting
confidence: 87%
“…This is followed by calcium-triggered exocytosis and subsequent endocytosis of the SV membrane, and concluded by recycling to replenish the SV pool and to sustain the vesicle cycle (Chua et al, 2010 ; Gundelfinger and Fejtova, 2012 ; Südhof, 2012 ). These various functions are executed by several overlapping sets of molecular machineries, which are dynamically assembled into a core macromolecular scaffold within the AZ (Chua, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Synaptic transmission is mediated by the regulated release of neurotransmitters from presynaptic nerve terminals ( Figure 1 ). Before release, neurotransmitters are stored in small trafficking organelles, termed synaptic vesicles, some of which are docked to specialized regions of the presynaptic plasma membrane known as active zones [ 12 , 13 ]. Upon arrival of an action potential, Ca 2+ ions enter the nerve terminal and trigger exocytosis of synaptic vesicles.…”
Section: An Overview Of Membrane Traffic In Presynaptic Nerve Termmentioning
confidence: 99%
“…Proteins directly involved in vesicle exocytosis such as the SNARE proteins (syntaxins, synaptobrevins and SNAPs), the calcium sensor synaptotagmin, V-ATPase and vesicular neurotransmitter transporters (VGLUT and VGAT) were all detected. Similarly, AZs that demarcate sites of neurotransmitter release by recruiting SVs and voltage-gated Ca 2+ channels also comprise of a large ensemble of proteins including AZ proteins such as RIM, RIM-BP, Munc13, ELKS/CAST/ERC and α-liprin that participate in SV docking and priming (Südhof, 2012 ; Chua, 2014 ). While this complexity and diversity of proteins in the presynapse has long been appreciated, we are only starting to unravel the principles underlying the movement of these cargoes to and away from these sites.…”
Section: Molecular Complexity Of Synapses and Challenges For Synapticmentioning
confidence: 99%